PENERAPAN TEKNIK ECOPRINT SEBAGAI MEDIA PERKEMBANGAN FISIK MOTORIK HALUS SISWA PAUD KELOMPOK A - Riyadlotus Sholichah; Endang Rahayu (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
One of the activities that trains the physical development of fine motor skills in children is tracing. In its application, tracing still uses conventional methods which are less attractive to children, so more innovative learning media are needed. The ecoprint technique is a technique for tracing on cloth that can be used as a learning medium. The purpose of this study was to find out how the ecoprint technique was applied as a medium for the physical development of group A's fine motor skills. This study used a qualitative method with a descriptive approach. Primary data sources in this study were observations of the implementation of activities and results of interviews with group A teachers. Meanwhile, secondary data sources came from school documents and archives. The collection techniques used were observation, interviews, and documentation. The data analysis technique uses the qualitative data analysis model of Miles and Huberman. The results of the study showed that the application of the ecoprint technique could assist in training the fine motor physical development of group A. This indicated that the ecoprint technique could be used as an alternative to tracing.